Traditional Treatment of Tawar Penggel in Karo Community - Perangin-Angin, Rivai Friyendi; Fikarwin Zuska (Indonesian Journal of Medical Anthropology, 2021)
This study examines the traditional treatment of Tawar Penggel from the Karo community which is still used today. The purpose of this study is to determine the process of inheritance and traditional treatment of Tawar Penggel and how to maintain it so that it is preserved as a culture, and to find out why people choose this treatment, especially the people of Jinabun Village, Kutabuluh Simole District. The method used is an ethnographic method with data collection techniques through in-depth interviews and observation, where researchers go directly to the field and live with the community to obtain accurate information. The results showed that Tawar Penggel's treatment process for patients from the beginning of treatment until they recovered without experiencing disabilities so that people still believed in traditional treatment. In addition, it also shows the history and descent from ancestors until now, where traditional medicine begins with traditions derived from habits by previous ancestors and also a culture.